Musigramas : sobre música y literatura en la narrativa de Marcelo Cohen - Chiani, Miriam Neri (2013)
El artículo procura demostrar que la producción narrativa de Marcelo Cohen exhibe, desde sus inicios en 1973, una inscripción regular, heterogénea y múltiple de ocurrencias musicales. Estos diversos modos de inscripción harían de su escritura una particularmente anafórica de tal práctica semiótica, que la música se convertiría en un metalenguaje de la literatura y esta, en un lenguaje interpretante de la música. Tal relectura de su obra responde al vacío de la crítica, que no se ha centrado en el tema, pues solo existen comentarios menores, aislados, en trabajos que no tienen por objeto esta cuestión y focalizados en algunos textos y no desde una perspectiva general que contemple su poética.
The present article aims to demonstrate that the narrative production of Marcelo Cohen has presented, from its beginnings in 1973, a regular, heterogeneous and manifold inscription of musical occurrences. These diverse forms of inscription tend to make his writing a particular kind of anaphoric reference to this semiotic practice, such that music becomes a metalanguage of literature, while the latter language becomes in its turn an interpretant of music. Such a rereading of his work responds to a gap in the existing criticism, which has not focused on this topic: only minor, isolated comments exist, in studies which do not address this issue and which discuss only certain texts, neglecting an overall view which would take into account the author's poetics.
Keywords: Literatura y música; Narrativa argentina contemporánea; Poética de autor; Marcelo Cohen; Comparatismo; Diálogos interartísticos; Literature and music; Contemporary argentine narrative; Author's poetics; Comparative studies; Dialogues between the arts; Marcelo Cohen